Anterior transposition of inferior oblique for inferior rectus muscle aplasia - Singh, Anupam (Taiwan J Ophthalmol, 2019)
Congenital absence of extraocular muscle is rare. The most common extraocular muscle found to be congenitally absent is superior oblique followed by inferior rectus. Patients with absent inferior rectus muscle can present with abnormal head posture and incomitant hypertropia with limitation of ocular motility in the field of action of the inferior rectus with or without torticollis. Microphthalmos, microcornea, coloboma, and Axenfeld–Rieger syndrome are known to be commonly associated with inferior rectus muscle aplasia. Orbital computed tomography (CT) or magnetic resonance imaging before surgery is useful for confirmation of the diagnosis and plan of management. We report satisfactory surgical outcome of anterior transposition of inferior oblique in a case of inferior rectus aplasia with iris coloboma, microcornea, and anomalous insertion of inferior oblique. The patient had right hypertropia in primary position which increased on levoversion and left tilt. Preoperative orbital CT revealed congenital absence of inferior oblique. Peroperatively, congenital absence of inferior rectus was confirmed, and inferior oblique was found to be hyperplastic and abnormally inserted to the sclera. Anterior transposition of inferior oblique was done with satisfactory outcome.